Bosnia and Herzegovina : Technical Assistance Report-Government Finance Statistics Mission. (IMF Staff Country Reports; Country Report ;, 2018)
This Technical Assistance Report discusses the recommendation made by the IMF mission to support the authorities of Bosnia and Herzegovina in improving government finance statistics (GFS) for decision making. The mission recommends that the authorities give consideration to the full list of objects, whereby Bosnia and Herzegovina can successfully compile GFS on an organized and comprehensive basis and within a designated amount of time. As a first step, the authorities will review the object list. As a second step, the mission together with the authorities will attach projected timelines/milestones to each lowest level object. If an object is already in place, then it will be noted as complete, and no further action will be needed.